Identificação automática dos parâmetros elétricos de motores de indução trifásicos - Azzolin, Rodrigo Zelir (2008)
This work presents an algorithm able to identify all electrical parameters of three phase induction motor, with discrete realization, using a fixe-point digital signal processor based platform. Some techniques presents in the literature are analyzed for comparison and validation with proposed algorithm. Initially, an historical review about the main parameter identification algorithms is accomplished and then, is obtained the models for an induction motor. From the machine model, two parameters identification algorithms are designed: a classical RLS identification, which is widely used in literature and a robust model reference adaptive controller, objecting to ponder the unmodeled dynamics. In the development of this work are displayed simulation results using the Matlab® software, real-time simulation in DSP platform, and finally, experimental results. After this results analysis, it is possible to determinate which of results these identification techniques better represent the behavior of three phase induction motor analyzed.